Antigen binding triggers long-range conformational changes in monoclonal antibodies - Bianchi, Davide; Saporiti, Simona; Palinsky, Wolf; Ben Mariem, Omar; Rossi, Mara; Eberini, Ivano; Centola, Fabio (Frontiers in Immunology, 2026)
IntroductionAntigen binding in monoclonal antibodies (mAbs) is traditionally associated with target recognition, but emerging evidence suggests it may also modulate antibody conformation and effector functions. Understanding how antigen engagement impacts the structural organization of therapeutic antibodies and their interaction with immune receptors is essential for optimizing antibody-based therapies. In this study, we investigated, via computational approaches, how antigen engagement alters the structural organization of therapeutic IgG1s and influences their ability to interact with FcγRIIIa.MethodsAccelerated molecular dynamics simulations were performed to investigate the structural and dynamic consequences of antigen binding in two therapeutic mAbs, adalimumab and avelumab. These antibodies were analyzed in different glycosylation states to capture the influence of post translational modifications.ResultsThe results revealed consistent long-range dynamic correlations between antigen-binding regions and distant domains within the Fc, suggesting an allosteric communication network involving the entire antibody structure and mediated by the antigen binding. Antigen engagement was found to increase the exposure of Fc residues critical for immune receptor recognition, an effect modulated by glycosylation and light chain isotype.ConclusionThese findings suggest that antigen engagement initiates a cascade of coordinated motions that reshape the mAb architecture and regulate its interaction with the immune receptors, offering new insights for the design of functionally optimized therapeutic antibodies.